Centro de Reinserción Urbano (2021)
The investigation of the project arises from one of the most evident problems in the country and prison overcrowding product of inadequate sos of "punishment" and resocialization, since the ha-proce-the current infrastructure lacks services and vital spaces for an adequate process. Therefore, the main intention of this project is to study how or of the current penitentiary prevents an adequate deprivation of liberty to the graduation of people from society, as people behaviors. because the productive and isolation and conditions in which they must serve their sentences are suitable for bad sentences